PENGARUH KEMAMPUAN PIMPINAN TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KERTANEGARA - ., Eliamas . (PREDIKSI, 2014)
This research aim to to know head of Â Ability have an effect on positive and signifikan to Job Spirit of Officer of Office of Subdistrict Tenggarong of Kutai Kertanegara.Data collected by Quesionery to 50 percentage of population or 38 people of responder of Officer of Subdistrict Tenggarong. Data collected to be analysed with the Simple Linear Regression test using the SPSS for windows Result of data analysis indicate that the Head Ability have an effect on positive and signifikan to Job spirit of Officer of Subdistrict Tenggarong, after known the Rhit 0,671 > rtab 0,320, and Assess the signifikansi of equal to 0.000 < 0,05.Value of R Square of equal to 0,450, its meaning Head Ability can influence the Job Spirit of Officer of Office of Subdistrict Tenggarong equal to 45,0 gratuity, while the rest 55,0 gratuity influenced Â the other;dissimilar variable which is not checked in this research. incoming Interpretation level of High categoryÂ